Physicochemical Characteristics of Carrot Chips (Dried Slices) with Differences in Temperature and Drying Time - Laily, Misbhatul; Asben, Alfi; Fahmy, Khandra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Carrots are one of the vegetable commodities that are rich in nutrients. This research is about drying carrots to extend the shelf life of vegetable products and maintain the nutritional content contained in carrots. Carrots are dried to produce a product like nutritious carrot chips. This research uses vacuum oven drying with different temperatures and drying times to determine the correct temperature and drying time to maintain carrot chips' nutritional content and physical appearance. The research design was a Completely Randomized Design (CRD) with two factors, namely drying temperature (50°C, 60°C, 70°C) and drying time (6 hours, 8 hours, 10 hours). Carrot chips with different temperatures and drying times significantly affected water content, total carotene, color index, and texture. Carrot chip products with vacuum oven drying at 60°C for 10 hours gave results with a water content of 4.24%, the highest total carotene value of 57.15 mg/100g, color appearance with an L* index of 35.68, a * of 20.91, b* of 17.63, texture value of 281.65 N/m2. As well as having organoleptic test results that were liked by the panelists regarding the color and texture of the carrot chips.